BIOPLASTIK NATA DE CASSAVA AS MATERIAL EDIBLE FILM ENVIRONMENTALLY FRIENDLY - Pratomo, Heru; Rohaeti, Eli (Jurnal Penelitian Saintek, 2015)
This research aimed to synthesize friendly plastic by using waste. Waste from cassava is made nata with using acetobacter xylinum. Characterizations of bioplastics were functional groups using IR, thermal properties using Differential Thermal Analysis, crystallinity using X-Ray Diffractometry, mechanical properties i.e. strength at break and strain at break, surface observing by using Scanning Electron Microscopy and biodegradation test using activated sludge. The primary component of nata de cassava was cellulose polymer. That is showed by functional groups i.e. –OH free, C-H allifatic, C-O, structure of piran ring, and È•-1,4-glikosidik link. That cellulose is supported by XRD diffractogram for film, film of nata de cassava had crystalline phase 1D and 1E at 15° dan 22,5°. The pellicle of cellulose is also supported SEM photo. Nata de cassava was stable film thermally, is showed by 20% of mass loss at 400°C. The biodegradation caused breaking of È•-1,4-glikosidik link until cellulose molecule dissociated to glucose molecules.